Self-Privacy Management of Generation Z on Social Media: A Study of Second Instagram Account Use - Hary Azis; Adelia Ismayana Nawawi; Fawzy Ismut Tawil; Nurliana; Rahmawati Hi. Nawir; Giska Mala Rahmarini; Donal Adrian (PT FORMOSA CENDEKIA GLOBAL, 2026)
Self-privacy on social media is an important aspect that every individual should protect. For university students who interact with diverse social groups, maintaining personal privacy can be achieved through various strategies, one of which is the use of a second Instagram account. This study aims to describe how university students in Palu City manage their self-privacy through the use of second Instagram accounts. The study employed a qualitative research design using a case study approach. Data were collected through observation and in-depth interviews and analyzed using data reduction, data display, and conclusion drawing/verification techniques. The findings reveal that the use of second Instagram accounts helps students maintain their personal privacy while still expressing their authentic identities. Students manage their privacy by limiting the number of followers on their second accounts and sharing personal experiences or emotions that may not align with social expectations after carefully filtering the content. In addition, second Instagram accounts serve as a means of supporting or clarifying information posted on their primary accounts, particularly when facing negative comments from other users, by allowing students to respond or provide clarification through the second account. Furthermore, the use of second Instagram accounts provides students with a space for self-reflection on their posts, encouraging them to develop more thoughtful and responsible online behavior.